Prevalence of bruxism in neurodegenerative disorders in the elderly: A systematic review and meta-analysis - JV Ashwin; Astha Singh; Mohit Kumar Shahi; Bhupendra Singh; Rama Appala Narasimha Reddy Challa (Industrial Psychiatry Journal)
Bruxism, characterized by the rhythmic grinding and clenching of teeth, is a common parafunctional behavior with implications beyond oral health. Recent interest has emerged in exploring its association with neurodegenerative disorders (NDDs), such as Parkinson’s disease (PD), Alzheimer’s disease (AD), and frontotemporal dementia (FTD). This systematic review and meta-analysis aimed to investigate the prevalence of bruxism in individuals with NDDs, synthesizing existing evidence and identifying areas for further investigation. A comprehensive search strategy was implemented across electronic databases (PubMed, Scopus, Embase, and Sci Info), supplemented by manual searches of reference lists. Studies were included based on predefined criteria related to bruxism and NDDs, with data extraction and quality assessment performed independently by two reviewers. Statistical analysis involved a meta-analysis using review manager software, with risk ratios (RRs) calculated to assess the association between bruxism and NDDs. Three studies were included in the meta-analysis, revealing a higher prevalence of bruxism in NDD subjects compared to controls (RR: 1.52; 95% CI: 1.33–1.71). Subgroup analysis indicated significant heterogeneity among studies, with no significant overall effect observed (Z = 0.41, P > 0.05). Neuroanatomical and neurobiological mechanisms linking bruxism and NDDs were explored, highlighting dopaminergic and serotonergic pathways’ roles. This meta-analysis provides evidence supporting a higher prevalence of bruxism in individuals with NDDs compared to controls. The findings underscore the need for further research to elucidate underlying mechanisms and inform clinical practice in managing bruxism and NDDs effectively.